2014
DOI: 10.1016/j.jecp.2014.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Stick with your group: Young children’s attitudes about group loyalty

Abstract: For adults, loyalty to the group is highly valued, yet little is known about how children evaluate loyalty. We investigated children's attitudes about loyalty in a third-party context. In the first experiment, 4- and 5-year-olds watched a video of two groups competing. Two members of the losing group then spoke. The disloyal individual said she wanted to win and therefore would join the other group. The loyal individual said she also wanted to win but would stay with her group. Children were then asked five fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
61
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(71 citation statements)
references
References 35 publications
8
61
0
1
Order By: Relevance
“…This is consistent with the finding from Kenward and Östh (2012) that 4-year-olds did not identify more with punishers than with non-punishers of first-order transgressors, and suggests that the propensity to value norm enforcement and enforcers may emerge between 4 and 5 years of age. This developmental shift is in line with other recent studies that have employed comparable methods and also found that whereas 5-year-olds demonstrate a robust grasp of rather sophisticated cooperation and group norms, 4-year-olds do not (Misch et al, 2014;. This developmental shift may reflect the fact that as children's interactions with strangers and peers and their experiences with group life (e.g., in kindergarten) increase, so too does their awareness of the importance of following and enforcing norms of cooperation (cf.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…This is consistent with the finding from Kenward and Östh (2012) that 4-year-olds did not identify more with punishers than with non-punishers of first-order transgressors, and suggests that the propensity to value norm enforcement and enforcers may emerge between 4 and 5 years of age. This developmental shift is in line with other recent studies that have employed comparable methods and also found that whereas 5-year-olds demonstrate a robust grasp of rather sophisticated cooperation and group norms, 4-year-olds do not (Misch et al, 2014;. This developmental shift may reflect the fact that as children's interactions with strangers and peers and their experiences with group life (e.g., in kindergarten) increase, so too does their awareness of the importance of following and enforcing norms of cooperation (cf.…”
Section: Discussionsupporting
confidence: 92%
“…This developmental shift may reflect the fact that as children's interactions with strangers and peers and their experiences with group life (e.g., in kindergarten) increase, so too does their awareness of the importance of following and enforcing norms of cooperation (cf. Misch et al, 2014;.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations